Quantitative flow cytometric monitoring of invasion of epithelial cells by Mycobacterium tuberculosis (2008)
Current methods for evaluating mycobacterial invasion of target cells pose technical difficulties including a long turn-around time. Thus, new methodologies must be developed that allow rapid and reliable monitoring of host cell invasion. Here, the invasion of A549 cell line by SYBR safe-labeled Mycobacterium tuberculosis (M. tuberculosis) H37Rv was assessed by flow cytometry and was expressed as the percentage of cells infected by M. tuberculosis. Over a third of A549 cells were invaded by M. tuberculosis, two hours after infection. The specificity of the invasion was confirmed in assays using red blood cells as target cells and Escherichia coli as the non-invasive bacterial control. These findings show that invasion of pulmonary epithelial cells by M. tuberculosis can rapidly and quantitatively be assessed with a great sensitivity by flow cytometric detection of SYBR safe-labeled M. tuberculosis.